Comparative therapeutic studies on experimentally infected mice and naturally infected calves with ringworm: Ouroba, M.S. brahim ,Saadi, A. G.Al-Samarrae and Jenan,M.K. Najim - brahim, Ouroba M.S. (The Iraqi Journal of Veterinary Medicine, 2009)
Groups of mice experimentally infected with ringworm Trichophyton mentagrophyte were treated withointments prepared from 5% cold alcoholic extract of two plants of Thymbra spicata , Ruta chalepnsisand compared with the commercial drug “Clotrmazole” (1%), recovery from ringworm needed 16 , 18 ,14 days for Th.spicata, Ruta chalepensis and Coltrmazole respectively.On the other hand 28 naturally infected calves with ringworm from the genera Trichophytonmentagrophytes and Aspergillus were divided into four groups, and each group treated individually withone of the ointments 5% concentration , cold alcoholic extract of Th.spicata and Ruta chalepensis beside“Clotrimazole”.The fourth group was left as a positive control groupRecovery from ringworm was complete after 21, 25, 18 days in the groups treated with spicata, Rutachalepensis and “Clotrimazole respectively. These results indicate the therapeutic effect of the coldalcoholic extract of the two plants used compared to commercial antifungal drug